Efek Logoterapi dan Psikoedukasi Kelarga terhadap Ketidakberdayaan Klien Penyakit Kronis di Rumah Sakit Umum - Niman, Susanti; Keliat, Budi Anna; Mustikasari, Mustikasari (Jurnal Keperawatan Jiwa, 2014)
Powerlessness in chronic diseases caused by physiological factors, medication management, process loss, lack of knowledge, health care systems, social issues, lack of resources beyond the individual, and cultural uncertainty (Lukbin & Larsen, 2013). The purpose of this final scientific work was to determine the effects of logotherapy and family psychoeducation to client’s powerlessness in chronic diseases were treated in public hospitals through Orems's Selfcare Model approach. Nursing implementations logotherapy and family psychoeducatiob provided to 17 clients with chronic illness who were treated 3-6 days and 7 clients were treated 1-2 days.The results of the implementation of logotherapy on the client and the caregiver's family psychoeducation may reduce signs and symptoms of powerlessness, increased ability to cope client and their families with powerlessness and selfcare. The mean increase in the ability of 17 clients who where treated 3 - 6 days higher than the 7 clients are treated 1-2 days. Scientific work is recommended for clients powerlessness due to chronic illness.